Temperature effect on optical properties of nickel (ii) phthalocyanine tetrasulfonic acid tetrasodium salt (NiPcTs) organic thin films - Abdulameer, Ameer F. (Iraqi Journal of Physics, 2019)
This study describe the effect of temperature on the opticalproperties of nickel(ii) phthalocyanine tetrasulfonic acid tetrasodiumsalt (NiPcTs) organic thin films which are prepared by spin coatingon indium tin oxide (ITO-glass). The optical absorption spectra ofthese thin films are measured. Present studies reveal that the opticalband gap energies of NiPcTs thin films are dependent on theannealing temperatures. The optical band gap decreases with increasein annealing temperature, then increased when the temperature risingto 473K. To enhance the results of Uv-Vis measurements and getmore accurate values of optical energy gaps; the Photoluminescencespectra of as-deposited and annealed NiPcTs thin films was studied.FTIR measurements for NiPcTs thin films also carried out in thiswork and gave good information about the NiPcTs bonds and itslocations as a compared with H2Pc as a reference.